Research on Bank Customers’ Cognition of Customer Retention Strategies Based on Empirical Analysis - Shinde, Sneha A; Kulkarni, Waman (Journal of Global Economy, Business and Finance, 2025)
In today's competitive economic environment, the banking industry has discovered the harsh reality that it must always search for ways to enhance its present banking system. The phrase "customer retention" refers to a bank's efforts to keep its customers for a certain amount of time. Customers are less inclined to switch banks if retention is strong. Customer retention is a continuous process for any firm, beginning with that initial point of contact and extending throughout the life of the connection and effective retention efforts based upon that relationship. This study is primarily directed to measure customer perception regarding customer retention strategies of the HDFC bank. A mixed - method research design is utilized, combining Descriptive cum exploratory research design. A questionnaire was prepared to analyse around 120 Bank customers for the primary investigation. There are mixed responses while asked about how much satisfied they are about the customer retention strategies adopted by the banks.